Positive Expectations: A Reflective Tale on the Teaching of Writing - Lolly Ockerstrom (Park University, 2007)
A case study on the teaching of writing, this paper discusses what motivates students in a freshman writing course to complete increasingly difficult writing assignments. The study provides a glimpse into how one class of freshman students developed positive expectations for writing a paper about a difficult poem by helping each other map strategies for reading and writing.